Teaching the Engineering Graphics of the Applicants for Higher Education by Means of Computer Modeling as a Scientific and Pedagogical Problem - Boyko, Vladislav; Goliiad, Irina; Hrytsenko, Larysa; Korchemna, Marina (International Journal of Engineering and Technology, 2018)
The article analyzes the state of graphic preparation of students of engineering specialties in accordance with the modern requirements regarding the professional activity of higher education graduates. The role of computer modeling as a means of training graduates of higher education in engineering graphics in pedagogical research from the didactic point of view is analyzed and substantiated.Â